"A Whole Hundred Years of Questionable Behavior": Wainwright/Garland/Jolson and Performance as Palimpsest - Kerr, Darin (The Theatre Annual, 2009)
Keywords: Audiences; Cultural heritage; Culture; Empowerment; History; Musical performances; Performance art; Prostheses; Theater

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing